(K-4)(k+2)=-8k-16

Simple and best practice solution for (K-4)(k+2)=-8k-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (K-4)(k+2)=-8k-16 equation:



(-4)(K+2)=-8K-16
We move all terms to the left:
(-4)(K+2)-(-8K-16)=0
We get rid of parentheses
(-4)(K+2)+8K+16=0
We multiply parentheses ..
(-4K-8)+8K+16=0
We add all the numbers together, and all the variables
8K+(-4K-8)+16=0
We get rid of parentheses
8K-4K-8+16=0
We add all the numbers together, and all the variables
4K+8=0
We move all terms containing K to the left, all other terms to the right
4K=-8
K=-8/4
K=-2

See similar equations:

| -2m+13=2m-1 | | 3=v-2/2 | | 1/3=z−5/12 | | 40=-4d+8 | | 2|3x+5|=-10 | | 25+10(-12-x)=5(2x+7) | | 85=5w-8 | | 2(t+17)=6 | | -8x-3x+9=10x-4x-8 | | 2(5m-8)-13=-7 | | 3v-v+1=5 | | Z^3+4z^2-25z-100=0 | | -10(8x+2)+8=2x+3 | | 3q-4q-6q-2=19 | | 9p=10p−8 | | 3-7n=25 | | 4=16/z | | 8x+1=7x+11 | | 5+k-5k=-4k-6 | | -6=5(v-6)-8v= | | 2=-7x+2 | | -1.6x=2(x+2.18) | | 2(1+6x)=146 | | Y+6.2x=-13x=4 | | 6j+2j=16 | | -6=5(v-6)-8v | | 18-3.8c=7.36-1.9c | | 7x-92+6x12=180 | | 9g-7g+4g-g=10 | | 7/5y-1=-4/3y-1/5 | | -2(4x+3)-x-7=46 | | -2x-+2=-6x+10x= |

Equations solver categories